THE AMAZING THERAPEUTIC PROPERTIES OF DHATURA-A SHORT REVIEW (AYUSHDHARA, 2015)
Plants have always played a major role in the treatment of human traumas and diseases worldwide. Dhatura is a widespread annual plant from the Solanaceae family. The species of Dhatura can be found throughout the world. The plant grows in sandy flats, plains, areas up to 2, 500 feet above sea level. Dhatura is one of the widely well known folklore medicinal herb. Dhatura is a plant with both poisonous and medicinal properties and has been proven to have great pharmacological potential with a great utility and usage as folklore medicine. In Ayurvedic text it is established as a poisonous plant but having good therapeutic properties after Shodhan process. After Shodhan process its poisonous properties are diminished but therapeutic properties get improved. So in most of the Ayurvedic preparations we use the Shudha Dhatura, Shudha vatsanabha, Shudha Bhanga etc. There are so many generic preparations available in old text to treat various diseases like sanity, gastric ulcer, fever, rhinitis, Bronchial asthma, seizures etc., having Dhatura as a main constituent. The phytochemical investigations showed the presence of saponins, tannins, steroids, alkaloids, flavonoids, phenols and glycosides. Atropine and scopolamine are competitive antagonists of muscarinic cholinergic receptors and are central nervous system depressants. This paper presents an exclusive review work on the traditional uses, Ayurvedic purification process, phytochemical, pharmacological actions of Dhatura.